Understanding the factors that influence Emirati women career development in Higher Education: Case Study from United Arab Emirates - ALRASBI, ABEER NAAJEM JUMAH BAHWAN (2017)
Several studies have discussed the position of women in higher education institutions internationally through investigating her career progression and the factors that influenced their advancement to senior leadership positions either in academic or administrative paths, yet, this body of literature lacks any studies on Emirati women’s career development in higher education in United Arab Emirates. The purpose of this research project is to explore the success trajectories of a representative sample of first generation Emirati women in a university case study who are currently in academic and administrative senior leadership positions in order to design a career development model that both accurately describes these paths and inspires Emirati women to pursue leadership positions in higher education institutions in United Arab Emirates. This study uses the perspectives of Super’s Life Span Life Space theory, Lent, Brown, and Hackett’s Social Cognitive Career theory, and Savickas’s Career Construction theory to explore early childhood and adulthood experiences, role model influence, mentoring and networking, and education system critical factors in shaping their career development journey, and the nature of their successful leadership experiences using a qualitative exploratory case study approach. The new model includes family, society, institutional, and governmental influencers. It also investigates other influences like religion, culture, extended family, and self-development.